2021
DOI: 10.1021/acs.cgd.0c01267
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Explosive Performance through Cocrystallization

Abstract: A 1:2 cocrystal of 4H,8H-difurazano­[3,4-b:3′,4′-e]­pyrazine and hydroxylamine has been prepared that displays 1,3,5-triamino-2,4,6-trinitrobenzene-like sensitivity and performance. Most notably, the detonation properties of the cocrystal are better than that of the hypothetical 1:2 physical mixture and also higher than the theoretically predicted salt, making this a rare example of a cocrystal in which the detonation properties are synergistic. This was achieved through maximizing the intermolecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Meanwhile, the synthetic route toward 4 was also achieved from the tetrazole-substituted pyrimidine (3). In this approach, 5-aminotetrazole was converted to its potassium salt first, since 5-aminotetrazole exhibits weaker nucleophilicity than hydroxylamine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the synthetic route toward 4 was also achieved from the tetrazole-substituted pyrimidine (3). In this approach, 5-aminotetrazole was converted to its potassium salt first, since 5-aminotetrazole exhibits weaker nucleophilicity than hydroxylamine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As the carrier of storing and releasing chemical energy, energetic materials play irreplaceable roles in civil construction and military defense. According to different applications, they can be divided into primary explosives, , booster explosives, propellants, and heat-resistant explosives. , Among them, heat-resistant explosives (HREs) are a class of energetic compounds with onset decomposition temperature exceeding 300 °C. Hexanitrosilbene (HNS) and 2,4,6-triamino-1,3,5-trinitrobenzene (TATB) are two well-known HREs, because of their high thermal stability. However, the relatively low detonation performance of HNS and high initiation requirements of TATB, somewhat restrict their broad applications .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the detonation performance of the ECC appears to be superior to theoretical prediction, providing it with synergistic properties. This is achieved by (i) appropriate pairing of the cocrystallizing molecules, (ii) developing setups that have H-donor and -acceptor sites, (iii) electron deficient and rich π-systems that ultimately result in an increase in the density of the consequent ECC through strong intermolecular interactions [ 69 ].…”
Section: New Energetic Cocrystalsmentioning
confidence: 99%
“…Novel organic radical platforms of highly stable organic radicals appear rarely and often require a unique combination of professional skill and creative search. Previously, 4 H ,8 H -bis­(furazano)­[3,4- b :3′,4′- e ]­pyrazine (H 2 L) was investigated in the chemistry of energetic materials only, and it was noted that its radical species can be obtained by oxidation with powerful oxidants like anhydrous nitric acid, fluorine, chlorine, or hot Caro’s acid . Recently, it was shown that in alkaline media, weaker oxidants may be used for the oxidation of H 2 L, and paramagnetic salts of alkali metal ions and ammonium with L were obtained .…”
Section: Introductionmentioning
confidence: 99%